Implementasi Metode TOPSIS untuk Meningkatkan Objektivitas Sistem Pendukung Keputusan dalam Pemilihan Pegawai Teladan - Sembiring, Elisabet Br; Tambunan, Esaday Gavinella Br; Siagian, Indah Enjelyna; Sembiring, Rafael Dekanta Yosafat; Ginting, Dewi Yohana br; Ginting, Lastri Marsely Br (Jurnal Sains dan Teknologi Informasi, 2025)
The selection of exemplary employees is an essential effort for organizations to improve performance, motivation, and work discipline. However, determining exemplary employees often encounters challenges due to subjectivity in the assessment process, which may result in decisions that do not fully reflect actual performance. To address this issue, a decision support system (DSS) is required to assist management in conducting evaluations objectively, systematically, and transparently. This study applies the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, which measures the relative closeness of each alternative to the positive ideal solution and the negative ideal solution. The evaluation criteria include discipline, responsibility, communication, initiative, and job mastery. The calculation stages consist of decision matrix normalization, weighted matrix formation, determination of ideal solutions, and preference value calculation to obtain employee rankings. The results indicate that the TOPSIS method produces consistent and fair outcomes in determining exemplary employees. From the ranking table, it is shown that the highest preference value of 0.6511 was obtained by alternative V8, namely Dermansyah, who is therefore concluded to be the most suitable candidate for the exemplary employee award. Thus, this research provides a practical contribution to organizations by offering an efficient and accurate decision-making tool that minimizes subjectivity. In the future, this system can be further developed by integrating additional methods or web-based technology to enhance accessibility and applicability in various organizational contexts.